Antioxidant, Cytotoxic Activity and Protein Target Inhibition of Ethyl Acetate Fraction Melinjo Seed (Gnetum gnemon L.) by In Vitro and In Silico Studies on HeLa Cervical Cancer Cells - Rawi Ingra Savitri; Nuha Haifa Arifin; Rifki Febriansah (Bogor Agricultural University, Indonesia, 2023)
Cervical cancer is one of the most common cancer suffered in women. Chemotherapy usage often causes physical and psychological side effects in patients. This study aims to determine the antioxidant and cytotoxic effects of the ethyl acetate fraction of melinjo seeds (Gnetum gnemon L.) on HeLa cervical cancer cells through in vitro and in silico assays. Melinjo seed was extracted by maceration using ethanol 70% and fractionated with ethyl acetate to obtain the Ethyl Acetate Fraction of Melinjo Seed (EAFMS). The identification of the active compounds group was done using Thin Layer Chromatography (TLC) method. In vitro studies were conducted on antioxidant tests using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method and cytotoxic activity test using 3-(4, 5-dimethylthiazolyl-2)-2, 5-diphenyltetrazolium bromide (MTT) Assay. In silico test for molecular docking analyzed by Autodock Vina method. The TLC analysis of EAFMS showed the presence of the stilbenoid compounds group. The antioxidant activity of EAFMS is weak, with an IC50 value of 175.8 g/ml. Cytotoxic activity of EAFMS is categorized as toxic to HeLa cancer cells with an IC50 value of 21.69 g/ml, while EAFMS has a synergistic effect combined with doxorubicin as a standard drug with a combination index (CI) value of 0.24-0.80. A molecular docking test of gnetin C with VHR receptor found a strong and stable bond with a docking score of -8.3 kcal/mol. Thus, EAFMS has the potential to be used as a chemopreventive agent for cervical cancer and can be combined with doxorubicin.